ACUTE MYOCARDIAL INFARCTION TRIGGERED BY DROWNING IN AN ELDERLY PATIENT: A CASE REPORT - Tan, Nguyen Van; Nguyễn Phan; Ngoc, Le Tran Bao (Journal of Health and Aging, 2025)
Drowning is a leading cause of unintentional injury-related mortality worldwide, particularly in two vulnerable populations: children and the elderly. In addition to respiratory compromise, drowning may lead to serious complications such as hypothermia, prolonged neurological injury, and cardiovascular sequelae — including myocardial damage. Myocardial infarction following drowning is rare and frequently overlooked in the acute setting, as elevated cardiac biomarkers are often attributed to resuscitation efforts. Nevertheless, in patients with pre-existing cardiovascular risk factors, systemic hypoxia combined with acute physiological stress induced by drowning may serve as a trigger for true myocardial infarction. This report describes an incidental finding of underlying coronary artery disease following a drowning event, underscoring the critical importance of comprehensive cardiovascular assessment in drowning survivors for early recognition of life-threatening cardiac events and timely, individualized management
Keywords: drowning; elderly patient; coronary artery disease